A Case of Livedoid Vasculopathy Successfully Treated with Sulodexide - Song, Chang Hwa (Ann Dermatol, 2020)
We report a 29-year-old female with a one-month history of non-healing multiple erythematous to violaceous plaques with crusts over both legs and feet. Tender, scarring ulcers with surrounding erythema were present. The clinical manifestation, together with histopathologic findings of fibrinoid plugs within vascular lumens and walls, as well as red blood cell extravasation, led to diagnosis of livedoid vasculopathy. The patient experienced recurrent painful violaceous plaques with ulcerations during the two years of treatment with oral pentoxifylline 400 mg three times daily. The cutaneous lesions and symptoms dramatically improved after the treatment regimen changed to oral sulodexide (250 lipasemic units) three times daily. Sulodexide, a highly purified mixture of glycosaminoglycans including dermatan sulfate and low-molecular weight heparin, could be an effective therapy for recalcitrant livedoid vasculopathy. Herein, we report a case of livedoid vasculopathy treated with sulodexide, which has not previously been reported.